Islam in Imperial China: sinicization of minority Muslims and synthesis of Chinese philosophy and Islamic tradition - Fathil, Fauziah (Universiti Sains Malaysia, 2019)
Even though China is nowhere near the heartland of Islam, the country is not a stranger to the religion brought by Prophet Muhammad (pbuh). In fact, Islam had reached China as early as 7th century ce and achieved its zenith during the era of the Ming Dynasty (1368–1644 ce), also known as the “Golden Age of Islam” in China. Not only were Muslims during the Ming era generally accepted by majority Chinese whose affiliations were predominantly Confucianism, Buddhism and Daoism, Islam was legally recognised by the imperial government. The number of Islamic institutions such as mosques and learning centres increased, and so did the number of Muslim population in the country. In administration and politics, the Muslims equally received their share while Muslim intellectuals and scholars found themselves appreciated and acknowledged by Chinese rulers for their contributions. Nevertheless, as with minorities of other countries, the Muslims in China were subject to assimilation or integration into the culture of the majority, i.e., Han Chinese. This policy known as “sinicization” consequently affected Muslims in many ways, leading to changes in their lifestyle, custom and tradition. Using qualitative approach and library research method, this paper aims to assess the underlying reasons for the sinicization of Chinese Muslims apart from the obvious political necessity of the Chinese imperial government, and the effects of the process on the Muslim community. On the latter, focus will be given to Muslims’ attempt to synthesise Chinese philosophy and Islam during the imperial era (618–1912 ce) as it served to project the peaceable nature of Islam hence enabled Muslims to preserve their distinctive Islamic identity and tradition amidst the predominant non-Islamic cultural setting. In other words, the synthesis which was pioneered by Chinese Muslim scholars, particularly of the Ming until the Qing era, not only prevented full assimilation of Muslims into local Chinese culture but also ensured the survival of Islam and its tradition in China until the modern period.